Influence of the Calcination Temperature on the Combustion Synthesized Perovskite LaMnO3 Compound - A.R. Shelke; N.G. Deshpande (Журнал нано- та електронної фізики)
A simple combustion method based on principles of propellent chemistry in which Polyvinyl alcohol (PVA) as fuel and nitrates as oxidizer were used for synthesizing the perovskite like LaMnO3 powders. The oxidizer to fuel ratio was maintained at 5 : 1. The darkish black powder obtained was calcined at 800 °C and 1000 °C for 5 hour. The combustion and thermal decomposition of the precursor were investigated using the TG-DTA and Fourier Transform Infra-Red (FT-IR) techniques. The X-ray diffraction (XRD) pattern of all three samples i.e., un-heated LaMnO3 powder (LMO-UH), calcined at 800 °C (LMO-800) and at 1000 °C (LMO-1000) were carried out. The single phase orthorhombic crystal structure was revealed to crystallize at LMO-800 and LMO-1000 with elevation in the crystalline size. A small impurity peak at 28.7° was seen of Mn3O4 for LMO-UH, which vanished after calcining it. The strong absorption in FT-IR spectra found at around 615 cm – 1 was due to the formation of metal-oxygen (M-O) bond. Moreover a small shift in this M-O bond with increase in calcination temperature suggested the strained LaMnO3 compound. Elemental analysis using the energy dispersive X-ray fluorescence spectrometer (EDXRF) indicated the presence of La and Mn with increase in the Mn contents after calcinations. The oxygen, nitrogen and hydrogen content in the sample were determined from the ONH analysis indicating a decrease in the oxygen content for LMO-800. Well defined porous-foam like morphology of the sample was achieved from scanning electron microscopic (SEM) study, which become compact with calcination process. Magnetic properties were found to transform from the ferromagnetic-to-paramagnetic phase for LMO-UH sample, while reduction in magnetization values and coercivity at low temperatures was obtained for LMO-800 and LMO-1000 samples.